(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2022)
Power inverter is an important device in nowadays technologies since the usage of renewable energy sources had been increased rapidly throughout the world. The main focus of research in power inverter field today is to produce a high efficiency power inverter to maximize the energy obtained from the renewable energy sources i.e. to reduce the energy losses. In DC to AC power conversion, the selection of appropriate switching scheme to be implemented is very crucial. In this paper, two different switching schemes, namely Nearest Level Modulation (NLM) and Selective Harmonics Elimination (SHE) are implemented on the Cross-Connected Sources Multilevel Inverter (CCSMLI) circuit with symmetrical configuration. The switching schemes are implemented on two different levels of CCSMLI circuit (11-level and 13-level) with two types of loads (R load and RL load). The performance of the circuit in terms of voltage Total Harmonics Distortion (THD) is being compared for different levels, load types and switching schemes. Simulation has been carried out using MATLAB/Simulink R2021a software package. The simulation results indicate a significant reduction in voltage THD when 13-level CCSMLI circuit, RL load and NLM switching scheme are implemented.